HIGH PRESSURE FLUIDS IN THE SYSTEM MGO-SIO2-H2O UNDER UPPER MANTLE CONDITIONS - Stalder R.; Ulmer P.; Thompson A.B.; Günther D. (My University, 2001)
Fluids and melts have been trapped and analysed in high pressure experiments in the model mantle system MgO-SiO2-H2O at 6 to 10.5 GPa and 900 to 1,200 °C. The fluid/melt traps consisted of a diamond layer that was added to the experimental charge and was separate from the silicate phases. The recovered diamond traps were analysed by laser ablation - ICP - MS. Starting materials were synthetic mixtures of brucite, talc and silica with variable Mg/Si containing 11-31 wt% H2O. Experiments on a serpentine starting composition [Mg3Si2O5(OH)4] result in MgO/SiO2 weight ratios in the subsolidus fluids close to 1 at 6 GPa and close to 2 at 9 GPa. Melt compositions at 6 and 9 GPa have MgO/SiO2 ratios close to that of forsterite. At a single pressure the amount of dissolved silicate in the fluid increases steadily with increasing temperature up to 1,150 °C, where a sudden increase of both SiO2 and MgO is observed. This discrete step marks the solidus, which is more clearly developed at 6 than at 9 GPa. Thus, hydrous melts within the model mantle subsystem Mg2SiO4-Mg2Si2O6-H2O are chemically distinct from aqueous fluids up to at least 9 GPa, corresponding to 300 km depth. Extrapolation of the current data set implies that total convergence between fluid and melt along the solidus probably occurs at 12-13 GPa (~400 km), i.e. close to the Earth's mantle transition zone. Beneath cratons, interactions of hydrous fluids with upper mantle lithologies cause relative silica depletion (olivine enrichment) at depths greater than 200 km and silica (orthopyroxene) enrichment at shallower depths.